Technology-Based Career Development Model for Improving Teacher and Employee Retention - Rasin Rasin (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to develop an integrated technology-based career development model and analyze its effectiveness in enhancing retention, motivation, and performance among teachers and employees in a private educational institution in Jakarta. The core objective is to address challenges posed by manual and non-transparent HR systems that undermine employee loyalty and productivity. Methodology/Approach: A qualitative case study was conducted at a private educational institution in Jakarta. Data were collected through in-depth interviews with nine purposively selected participants, including the HR Manager, principals, and teachers, as well as from policy documents and performance records. Data were analyzed using thematic, SWOT, and gap analyses, with validity ensured through triangulation of sources, methods, and theories. Results/Findings: The manual performance evaluation system lowers motivation and retention, while a proposed digital assessment model with LMS aims to address these gaps. Conclusions: The study introduces a conceptual and practical model for career development through digital tools to enhance motivation, retention, and job satisfaction. By aligning digital HR strategies with employee needs, the model offers actionable insights for institutions undergoing digital transformation. Limitations: As a single-case study, the findings are context-specific and lack generalizability. The model remains conceptual and requires further validation through large-scale implementation and quantitative monitoring. Contributions: This study contributes empirically to HRM literature, particularly in education, by providing a framework for designing technology-based career development models and offering practical strategies to transition from manual to integrated digital HR systems.